GENOMIC INSIGHTS INTO TASAR SILKWORMS: CORRELATION BETWEEN GENETIC VARIABILITY AND SERICIN QUALITY - Md Tahfizur Rahman,; Shagufta Nigar,; Mustafa Kamal Ansari, (The Bioscan, 2025)
Tasar silkworms (Antheraea mylitta) are crucial for the production of tasar silk, valued for its texture and quality. The role of genetic variability in determining the quality of sericin—a silk protein with significant industrial and biomedical applications—remains underexplored. This study delves into the genomic architecture of Tasar silkworm populations, correlating genetic diversity with sericin quality. Using advanced sequencing technologies, we identify key genetic markers associated with superior sericin properties, providing insights for improving sericulture practices.